Hyperbranched polymer-based nanoparticle drug delivery platform for the nucleus-targeting in cancer therapy - ALARÇİN, EMİNE (My University, 2023)
© 2023 Elsevier B.V.Hyperbranched polymers (HPB) are drawing attention as one of the drug delivery platforms that can encapsulate drugs owing to the internal voids in their three-dimensional construct. It is feasible to develop HBP-based nano-sized drug delivery platforms and improve the efficacy of cancer treatment due to its potential properties. In particular, the contribution of targeted drug delivery systems that can target malignant tissues in the treatment processes is undeniable. For this purpose, modifying an HBP-based nanoparticle delivery system with a targeting molecule is vital. In this study, we synthesized folic acid-modified HBP-based nanoparticles and their physical (DLS, zeta potential) and chemical (FTIR, NMR) characterizations were performed, and finally 5-Fluorouracil (5-FU) was loaded as a model active agent. The release properties (UV-VIS) and release kinetic models of 5-FU-loaded folic acid-modified nanoparticles were investigated in different pHs. In vitro cellular activities (MTT, cellular uptake) and targeting properties to the folate receptor (FR) were determined by flow cytometry on HeLa (FR, +) and L929 (FR, -) cells. According to all the results, folic acid-modified HBP-based nanoparticles were efficiently transported to the cell nucleus in the targeted FR + cells, and internalization of nanoparticles in HeLa cells is ∼2.5 times higher than L929 cells. All results suggest that folic acid modification to the nanoparticles is critical in folate receptor-positive cancer treatment.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; TROPİKAL TIP; Clinical Medicine (MED); CLINICAL MEDICINE; TROPICAL MEDICINE; Farmasötik bilim; Yaşam Bilimleri; Pharmaceutical Science; Life Sciences; 5-Fluorouracil; Cancer; Folic acid; Hyperbranched polymer; Targeted drug delivery